Peranan MSG Tempe, Nanas, dan Bayam Untuk Pemenuhan Gizi Baik - Widodo, Freedom Septian; Rachmayanti, Riza Azalea; Haqq, Auryn Zahran Nail (Madani: Jurnal Ilmiah Multidisiplin, 2024)
MSG is a commonly used flavor enhancer in the food industry. However, synthetic MSG is often associated with negative side effects. The use of monosodium glutamate (MSG) in the food industry has been a topic of debate in recent years due to concerns over its health effects. Therefore, this study aims to examine organic MSG produced from tempeh and pineapple with the addition of spinach as a substitute for MSG.  The advantage of this organic MSG is that it is much safer and healthier. There has been a significant increase in the production of tempeh every year, reflecting the growing interest in this product. In addition, tempeh and pineapple with added spinach proved to be a potential source for the production of organic MSG. The method used in this study was experimentation of tempeh and pineapple with added spinach. The findings provide new insights in the development of organic MSG from locally abundant raw materials such as tempe and pineapple with added spinach, while contributing to the understanding of the dynamics of tempe production. Further research is needed to explore the potential industrial applications of this organic MSG and understand its impact on sustainability and public health. The results showed that the preparation of tempeh and pineapple MSG with added spinach produced various organic compounds. In addition, this study showed that tempeh, pineapple, and spinach showed potential as MSG substitutes in culinary applications, by producing the desired umami flavor without the addition of synthetic MSG. This research makes an important contribution to the development of more natural and healthy alternatives to MSG.